Application of HBIM as a Research Tool for Historical Building Assessment - Dina Stober; Roko Žarnić; Davorin Penava; Margareta Turkalj Podmanicki; Romana Virgej-Đurašević (Salehan Institute of Higher Education, 2018)
The benefits and challenges posed by Building Information Modelling in documenting the existing buildings comes from the development of the digital support to the needs, compatibility and interoperability of applied technologies and at the same time of the available knowledge and skills to use a wide range of necessary technologies. Within the scope of Heritage Building Information Modelling, the use of 3D views has become a common practice, often hindered by complex geometry and layered time changes of constructive systems. Implementation of BIM for heritage buildings is developed through the procedures of designing parametric objects and selecting compatible technologies to create a rich information model. The paper presents the application of the 3D BIM approach in researching, documenting and interpreting the historic building of the baroque Palace of the Slavonian General Command in the historic core of Osijek, Croatia. Applied recording technologies, laser scanning, and thermal scanning, as support for HBIM, have been chosen according to selective research goals of the Palace of the Slavonian General Command. The method of simulating non-existent constructive elements from assumptions and analogies is presented as the preceding procedure of creating a HBIM library that opens the possibility of the broader dissemination of information on the explored heritage. The results point to the advantages of the model building approach for valorisation and interpretation of constructive changes over time, through the modelling logic, closely relating to the logic of construction.